2005
DOI: 10.1101/lm.94505
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis underlies post-retrieval memory consolidation to a restricted degree only when updated information is obtained

Abstract: Consolidation theory proposes that through the synthesis of new proteins recently acquired memories are strengthened over time into a stable long-term memory trace. However, evidence has accumulated suggesting that retrieved memory is susceptible to disruption, seeming to consolidate again (reconsolidate) to be retained in long-term storage. Here we show that intracortical blockade of protein synthesis in the gustatory cortex after retrieval of taste-recognition memory disrupts previously consolidated memory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
78
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 38 publications
11
78
0
Order By: Relevance
“…We predicted a key role for cholinergic transmission in memory destabilization because of the common finding that reconsolidation is prompted most reliably when novel information is available during the reactivation episode (Rodriguez-Ortiz et al 2005;Morris et al 2006;Rossato et al 2007;Winters et al 2009;Forcato et al 2010;Sevenster et al 2013). Indeed, ACh has long been implicated in cognitive functions linked to new learning (Sarter and Bruno 1997;Hasselmo and McGaughy 2004), and in vivo microdialysis studies demonstrate enhanced ACh release in various brain regions when animals explore novel environments or objects (Tang and Aigner 1996;Aloisi et al 1997;Giovannini et al 2001;Ihalainen et al 2010) or are otherwise aroused (Nilsson et al 1990;Inglis and Fibiger 1995) or attentionally taxed (Passetti et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted a key role for cholinergic transmission in memory destabilization because of the common finding that reconsolidation is prompted most reliably when novel information is available during the reactivation episode (Rodriguez-Ortiz et al 2005;Morris et al 2006;Rossato et al 2007;Winters et al 2009;Forcato et al 2010;Sevenster et al 2013). Indeed, ACh has long been implicated in cognitive functions linked to new learning (Sarter and Bruno 1997;Hasselmo and McGaughy 2004), and in vivo microdialysis studies demonstrate enhanced ACh release in various brain regions when animals explore novel environments or objects (Tang and Aigner 1996;Aloisi et al 1997;Giovannini et al 2001;Ihalainen et al 2010) or are otherwise aroused (Nilsson et al 1990;Inglis and Fibiger 1995) or attentionally taxed (Passetti et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, not all memories become labile when reactivated; boundary conditions, including the strength of initial memory encoding and the age of the memory at the time of retrieval, determine the likelihood of destabilization upon reactivation (Milekic and Alberini 2002;Eisenberg and Dudai 2004;Suzuki et al 2004;Winters et al 2009). These boundary conditions may be related to the putative role of reconsolidation in memory updating (Sara 2000;Rodriguez-Ortiz et al 2005;Morris et al 2006;Hupbach et al 2007;Rossato et al 2007;Lee 2009;Forcato et al 2010;Sevenster et al 2013). Accordingly, stronger or more remote memories may be less likely to be altered in the absence of salient novel information (Lee 2009;Winters et al 2009).…”
mentioning
confidence: 99%
“…However, in these experiments the cortical transfer occurred 3 -4 wk after the initial acquisition. As we have already mentioned, a well-learned memory does not undergo reconsolidation unless in the presence of new information to update it (Rodriguez-Ortiz et al 2005;Morris et al 2006;Winters et al 2009). However, the possible involvement of neocortical regions in the case of strong hippocampus-independent memories has never been explored in the case of spatial memory reconsolidation.…”
mentioning
confidence: 98%
“…Even though Tronel et al (2005) concluded that reconsolidation was not required to link new information to a retrieved memory, Lee (2008) demonstrated that an adaptive function of the reconsolidation process enables the update of memory's content. Without the presence of new information, thus when updating is not necessary, a very well-learned memory does not undergo reconsolidation (Rodriguez-Ortiz et al 2005;Winters et al 2009). …”
mentioning
confidence: 99%
“…Behaviorally, safe taste memory trace formation is observed by a gradual increase in the intake of flavored-water solution as a function of the number and the duration of prior periods of access to the solution and it was termed Attenuation of Neophobia (AN) (Domjan 1976) or safe Taste Recognition Memory (Bermudez-Rattoni 2004). Taste familiarization has been shown to be a gradual, updatable process dependent on several rounds of protein synthesis in the IC upon reactivation (Rodriguez-Ortiz et al 2005). Also, it has been shown with a number of distinct methods that the activity of tasteresponsive neurons in the IC can be modified with learning (Yasoshima and Yamamoto 1998;Bahar et al 2004;Accolla and Carleton 2008).…”
mentioning
confidence: 99%